2011
DOI: 10.1021/es200506b
|View full text |Cite
|
Sign up to set email alerts
|

Are Carbon Nanotube Effects on Green Algae Caused by Shading and Agglomeration?

Abstract: Due to growing production, carbon nanotubes (CNT) may soon be found in a broad range of products and thus in the environment. In this work, an algal growth test was developed to determine effects of pristine and oxidized CNT on the green algae Chlorella vulgaris and Pseudokirchneriella subcapitata. CNT suspensions were prepared in algal test medium and characterized taking into account the suspension age, the reduced light transmittance of nanoparticle suspensions defined as shading of CNT and quantified by UV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
162
2
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 293 publications
(185 citation statements)
references
References 33 publications
18
162
2
3
Order By: Relevance
“…This is supported by previous work reporting that SWCNT toxic effects on the green algae Pseudokirchneriella subcapitata were lost with higher concentrations of the surfactant Gum Arabic [36]. In another study, Schwab et al found that carbon nanotubes only partially dispersed by natural organic matter had no direct toxic effect but that agglomerated nanotubes have indirect effects [37]. Therefore, it is likely that very welldispersed and nonagglomerated SWCNTs do not have any toxic effect, as is described herein.…”
Section: Effects Of Swcnt and Dispersion On Algal Growthsupporting
confidence: 88%
“…This is supported by previous work reporting that SWCNT toxic effects on the green algae Pseudokirchneriella subcapitata were lost with higher concentrations of the surfactant Gum Arabic [36]. In another study, Schwab et al found that carbon nanotubes only partially dispersed by natural organic matter had no direct toxic effect but that agglomerated nanotubes have indirect effects [37]. Therefore, it is likely that very welldispersed and nonagglomerated SWCNTs do not have any toxic effect, as is described herein.…”
Section: Effects Of Swcnt and Dispersion On Algal Growthsupporting
confidence: 88%
“…Interestingly, much work has focused on the research and development of applications of CNTs, but only a few studies have focused on the behavior and risks associated with CNTs in environmentally relevant conditions (Petersen et al, 2011;Hutchison, 2008;Wang et al, 2008;Robichaud et al, 2005;Lecoanet et al, 2004). Preliminary ecotoxicity studies have shown that CNTs are toxic to algae, fish, daphnids and other organisms (Schwab et al, 2011;Petersen et al, 2009;Smith et al, 2007). Transport studies showed that humic acid, a common environmental constituent, dispersed CNTs and increased their mobility in the environment (Wang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…While purified CNTs may contain only a small percentage of the metal catalysts, raw CNTs can contain as much as 40% metal by weight. To date little work has been done to quantify the release of metal residues from CNT matrices in natural waters, or the toxicological implications of the bioavailable metals (Schwab et al, 2011;Hull et al, 2009;Blaise et al, 2008). It was previously thought that CNT purification removed almost all metals that could leach in solution, but there may be some residual metals since metal dissolution is kinetically limited and most purification processes are too short in duration (Liu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4.12 Shading control: The purpose of this control is to assess the extent to which light intensity reduction caused by ENMs could impact the ecotoxicity endpoint measured (17,18). The first step is to analyze the decrease in the transmittance through the test container containing the ENM from the specified light source; this could be conducted at the highest ENM concentration or at a range of ENM concentrations if a dose-response relationship is being tested.…”
Section: Nutrient Depletion Controlmentioning
confidence: 99%